"Люди місячного світла" у Біблії: заклик до знищення чи заклик до сумління? - Чікарькова, М.Ю. (Наука. Релігія. Суспільство, 2013)
У статті досліджено біблійне табу на гомосексуальність, яке, руйнуючи стереотипи язичницького мислення, піднесло інтелектуальну схему Чоловіче / Жіноче на противагу стихійному поклонінню будь-якій сексуальності. Водночас гомосексуальність не є «протиприродним» явищем, бо Природу (Творіння) не ототожнено з Богом (Творцем); Божий задум порушується бунтом Творіння проти Творця. У Біблії є й певні «нестиковки» в тлумаченні проблеми, визначені перебігом історико-культурних обставин. Та переважає погляд, згідно з яким слід засуджувати гріх, а не грішника. В статье исследовано библейское табу на гомосексуальность, которое, разрушая стереотипы языческого мышления, противопоставило интеллектуальную схему Мужское / Женское стихийному поклонению любой сексуальности. Одновременно гомосексуальность не является «противоестественным» явлением, потому что Природа (Творение) не отождествлена с Богом (Творцом); Божий замысел нарушается бунтом Творения против Творца. В Библии есть и определенные «нестыковки» в толковании проблемы, определенные переменой историко-культурных обстоятельств. Но преобладает взгляд, согласно которому следует осуждать грех, а не грешника. This paper investigates the roots of the taboo on homosexuality embedded in the Bible, which is trying to break down stereotypes pagan thinking, presented an ideal intellectual scheme binary opposition Male / Female as opposed to spontaneous worship to every sexuality that defined the entire structure of the Judeo-Christian culture. However, homosexuality is «unnatural» phenomenon because Nature (Creation) in Bible does not identify with God (Creator), in the material reality of God's plan is often violated in rebellion against the Creator of Creation. In the Bible, there are also some «inconsistencies» in the interpretation of the issues identified by the course of historical and cultural circumstances of life of the ancient Jews. Anyway, there prevails a view according to which should condemn the sin and not the sinner, and it is not always clear how the traditional society and our contemporaries. Acute urgency of the problem is obvious, especially if you consider that we are talking about millions of maimed and tragic fate of situations and our society to realize this problem is not ready.